2004
DOI: 10.1021/ja047875o
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking Protein−Protein Electron Transfer:  Voltammetry ofPseudomonas aeruginosaAzurin and theThermus thermophilusCuADomain at ω-Derivatized Self-Assembled-Monolayer Gold Electrodes

Abstract: Well-defined voltammetric responses of redox proteins with acidic-to-neutral pI values have been obtained on pure alkanethiol as well as on mixed self-assembled-monolayer (SAM) omega-derivatized alkanethiol/gold bead electrodes. Both azurin (P. aeruginosa) (pI = 5.6) and subunit II (Cu(A) domain) of ba(3)-type cytochrome c oxidase (T. thermophilus) (pI = 6.0) exhibit optimal voltammetric responses on 1:1 mixtures of [H(3)C(CH(2))(n)()SH + HO(CH(2))(n)()SH] SAMs. The electron transfer (ET) rate vs distance beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
138
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(156 citation statements)
references
References 59 publications
(112 reference statements)
18
138
0
Order By: Relevance
“…With mercaptoundecanoic acid, in contrast, the anodic and cathodic signals were no longer observed, suggesting a larger decrease in the ET. These results are consistent with previous studies on mitochondrial cyt c [7,9,17] as well as other small soluble proteins [61,62], which showed an almost distance-independent measured rate for short-length thiols (C1-C10) and an exponential decrease of the ET rate for longer ones. We also note that the width of the peaks is larger for the proteins immobilized on mercaptohexanoic acid than on mercaptopropionic acid.…”
Section: Cyclic Voltammetrysupporting
confidence: 93%
“…With mercaptoundecanoic acid, in contrast, the anodic and cathodic signals were no longer observed, suggesting a larger decrease in the ET. These results are consistent with previous studies on mitochondrial cyt c [7,9,17] as well as other small soluble proteins [61,62], which showed an almost distance-independent measured rate for short-length thiols (C1-C10) and an exponential decrease of the ET rate for longer ones. We also note that the width of the peaks is larger for the proteins immobilized on mercaptohexanoic acid than on mercaptopropionic acid.…”
Section: Cyclic Voltammetrysupporting
confidence: 93%
“…Trp48 is nestled in a hydrophobic pocket of the protein and thought to be important in long-range charge transfer in azurin [185]. In further studies, Trp48 has proven necessary for redox activity in azurin mutants [186] and shows significant fluorescence quenching in the presence of copper [187], further demonstrating the profound effect of protonation state on tryptophan-mediated charge transfer. The properties of indoles and their capacity to engage in both concerted and stepwise PCET afford these species great flexibility as electron-shuttle residues in redoxactive proteins; model systems allow for close examination of the subtleties pertinent to both concerted and stepwise PCET pathways and their consequences.…”
Section: Indolesmentioning
confidence: 87%
“…1A shows a schematic representation in which the hydrophobic patch around the copper center in azurin is spatially and chemically suitable for coupling to the terminal methyl group of the alkanethiol. Mutagenesis experiments showed that the mutation of the tryptophan 48 (Trp 48) to other residues in azurin results in complete quenching of interfacial ET (38). Trp 48, which is not supposed to interact physically with the methyl group of the alkanethiol, thus appears still to play an important role in establishing the electronic coupling of azurin to the electrode surface (38).…”
Section: Methodsmentioning
confidence: 99%
“…Mutagenesis experiments showed that the mutation of the tryptophan 48 (Trp 48) to other residues in azurin results in complete quenching of interfacial ET (38). Trp 48, which is not supposed to interact physically with the methyl group of the alkanethiol, thus appears still to play an important role in establishing the electronic coupling of azurin to the electrode surface (38). The wild-type protein molecules are confined well by hydrophobic interactions to form a monolayer with the copper center facing the electrode surface (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation